Ochrona zabytków w prawie administracyjnym. Wybrane zagadnienia - Babiarz, Stefan (Kwartalnik Prawa Podatkowego, 2016)
The provisions of the Act on protection and care of historical monuments set forth the obligation for conservator bodies to issue a number of documents, such as: conservator’s recommendations, conservator’s guidelines, permit for performance of construction and conservator’s work, division of immovable historical monument and the obligation of owners (holders) of historical monuments, in case of utility development of a historical monument, to hold documentation defining, among others, the state of its preservation, adaptation possibilities, including the scope and manner of performance of conservator’s works. In fact, none of the provisions of the act specify the obligation for such conservator bodies to issue a document presenting the factual state of an immovable or movable historical monument. Such a document may constitute conservator’s recommendations, as long as the conservator of historical monuments provides in the document such state or the certificate referred to in Art. 217 of the Code of Administrative Procedure. However, the certificate is regulated by the provisions of the Code of Administrative Procedure, and not in the provisions on the protection and care of historical monuments. It is of importance because the provisions on tax exemptions contained in the acts on selfgovernmental taxes set forth that the state of development, maintenance, conservation or protection should be defined in accordance with the provisions on protection and care of historical monuments.